2020
DOI: 10.1038/s41598-020-76555-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and methylome analysis reveals three cellular origins of pituitary tumors

Abstract: Pituitary adenomas (PA) are the second most common intracranial tumors. These neoplasms are classified according to the hormone they produce. The majority of PA occur sporadically, and their molecular pathogenesis is incompletely understood. The present transcriptomic and methylomic analysis of PA revealed that they segregate into three molecular clusters according to the transcription factor driving their terminal differentiation. First cluster, driven by NR5A1, consists of clinically non-functioning PA (CNFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 44 publications
5
42
0
2
Order By: Relevance
“…Our results underscored the participation of spliceosome components in the molecular machinery of the pituitary tumors pathogenesis derived from POU1F1and NR5A1-cell lineages and the alteration of the mRNA splicing patterns characteristic to each tumor. These tumor-specific spliceosome components and mRNA isoforms generated could support the notion that the pituitary tumors arise from divergent cell lineage origins or that they develop from partially committed pituitary stem cells, previously proposed by our group [10,11]. Similar results where the upregulation of several splicing factors in tumor-specific manner being observed in PA [12].…”
Section: Discussionsupporting
confidence: 88%
“…Our results underscored the participation of spliceosome components in the molecular machinery of the pituitary tumors pathogenesis derived from POU1F1and NR5A1-cell lineages and the alteration of the mRNA splicing patterns characteristic to each tumor. These tumor-specific spliceosome components and mRNA isoforms generated could support the notion that the pituitary tumors arise from divergent cell lineage origins or that they develop from partially committed pituitary stem cells, previously proposed by our group [10,11]. Similar results where the upregulation of several splicing factors in tumor-specific manner being observed in PA [12].…”
Section: Discussionsupporting
confidence: 88%
“…However, these highly proliferative carcinomaresembling tumors do not immediately draw a parallel with the typically benign tumors that occur in the pituitary. Finally, a recent study, clustering pituitary tumors by RNA-seq analysis in three groups coinciding with canonical lineage transcription factors [i.e., TBX19, NR5A1 (SF1) and POU1F1 (PIT1)], did not reveal a transcriptomic link with the (normal) stem cell population, but suggested that the "tumor progenitor cells" (TSC) derive from already (partially) committed cells expressing the respective transcription factor (99).…”
Section: Pituitary Stem Cells During Tumorigenesis In the Glandmentioning
confidence: 99%
“…Altered expression of lncRNAs is likely to underlie diverse cell phenotypes and behavior including oncogenesis, and several studies have examined their differential expression and possible functions in gonadotrope or nonfunctioning adenomas (NFPAs) which are primarily of gonadotrope origin ( 140 , 141 ). Analysis of the coexpression networks for lncRNAs and mRNAs in these tissues, compared with normal pituitary tissue, suggested that each lncRNA might have a large number of mRNA targets ( 142 , 143 ) and exposed lncRNAs that appear to play a role in tumor formation or invasiveness, while some of their targets are known to play roles in normal gonadotrope function.…”
Section: Regulatory Lncrnas In Nonfunctioning Pituitary and Gonadotrope Adenomasmentioning
confidence: 99%